Complete remission of Hodgkin’s lymphoma in a pediatric patient with TTN gene mutation treated with brentuximab vedotin combined chemotherapy without anthracyclines: A case report - Li, Ying; Liu, Ligang; Sun, Hao; Li, Nan; Huang, Shuang; Olinger, Alexander; Xu, Xiaolin; Wang, Xiaoling; Duan, Yanlong (Frontiers in Oncology, 2022)
Introduction: There is no guideline for the treatment of Hodgkin’s lymphoma (HL) in pediatric patients with titin (TTN) gene mutation and heart failure. We explored the feasibility of using Brentuximab Vedotin (BV) plus chemotherapy without anthracyclines to treat one pediatric HL patient with TTN mutation. Case presentation: A 5y7m male patient was admitted to the hospital due to high fever and shortness of breath. He was diagnosed with Stage IV IVB high-risk Hodgkin’s lymphoma (lymphocyte-depleted type) at admission. Echocardiography showed the left ventricular ejection fraction (LVEF) was 27%. The gene sequencing revealed a pathogenic variant in the TTN gene. Due to the risk of cardiotoxicity of anthracycline, he received 6 cycles of chemotherapy (no anthracyclines), 4 cycles of them plus BV with dosing 1.8 mg/kg, q3w. The tumor was reduced by 77% after 2 cycles of BV and 4 cycles of chemotherapy. At the end of 4 cycles of BV and 6 courses of chemotherapy, with complete remission achieved, the tumor was reduced by 85%. After 11 months of follow-up, the patient was still in complete remission with no adverse events reported, as well his LVEF improved to 62%. Conclusion: The combination BV with chemotherapy is effective and well-tolerated for pediatric HL patients with TTN gene mutation.